Talent Management Implementation as a Step Towards Creating a Competitive Advantage for The Company - Hartanto Halim (Ekonomis: Journal of Economics and Business, 2023)
Organisations face problems in personnel management in this dynamic and competitive business environment. For businesses that function at an international level, talent management is becoming increasingly important. Bank Rakyat Indonesia (BRI) needs competent and qualified human resources, especially in this era of globalisation. Human resources are one of the most important assets owned by the company, because no matter how much the company produces capital but if it is not in motion by human labour, it will not be an added value for the company. Data collection is done with a qualitative approach that tries to get a better understanding of the complexity in human interaction. Bank Rakyat Indonesia (BRI) needs competent and qualified human resources, especially in this era of globalisation. Human resources are one of the most important assets owned by the company, because no matter how much the company produces capital but if it is not in motion by human labour, it will not be an added value for the company. Career development based on performance management refers to the provisions governing the career path of workers. Mutations are carried out based on the needs of the company, the length of service of workers in a particular work unit and the performance of the workers concerned. In performance management, Bank BRI assesses performance from 2 (two) sides, namely the achievement of key performance indicators (KPIs) and the achievement of competencies with the aim that HR performance evaluation measures in a balanced manner what must be achieved and how to achieve it. The stages of Bank BRI's performance management system are also systematically designed consisting of planning, guidance and evaluation.